THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEMS AND LEADERSHIP STYLE ON BUMDES PERFORMANCE (Empirical Study of BUMDes in Rokan Hulu Regency) - Nurlian, Tri; Desmiyawati; Suci Nurulita (UPT Publikasi Ilmiah UNISBA, 2024)
Village-owned enterprises (BUMDes) have an essential role in improving the economy of a village by developing suitable governance. This study aims to examine the effect of accounting information systems and leadership style on the performance of BUMDes. This research is quantitative; the primary data is used, and data collection is done directly using a questionnaire. The sample in this study consisted of 168 respondents. Data analysis was performed using multiple linear regression with SPSS 26. The results obtained from this study are that the accounting information system and leadership style affect the performance of BUMDes. Keywords : Accounting Information Systems, Leadership Style, Performance of BUMDes.